ANALISIS MODUS DAN MITIGASI PENCEGAHAN KORUPSI ANGGARAN MELALUI PROSES PENGADAAN BARANG DAN JASA (PBJ) DI JAWA TENGAH - Hardiwinoto . . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
The aims of this study are to analyze two things, namely: a) to analyze the occurrence of budget corruption modes and mechanisms through PBJ; b) analyzing the amount of the corrupted budget through the PBJ; and developing a mitigation instrument for preventing budget corruption through the PBJ. The analysis method is used through four stages, namely: a) literature study, compilation of various cases of budget corruption; b) investigations related to the mode and mechanism of budget corruption, especially in the PBJ process; c) analysis of budgetary corruption mechanisms in the PBJ process; and d) develop instruments for preventing budget corruption in the PBJ process. The results of the analysis found that 18 corruption conspiracy mafias through the PBJ process involved legislative, executive and vendor elements. Corruption is carried out in a planned and systematic manner through the PBJ process. Up to 80% of cases of budget corruption through the PBJ process occur